1993
DOI: 10.1097/00006676-199307000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Human Periodic Interdigestive Gastrointestinal Motor and Pancreatic Function by the Ileum

Abstract: Following ingestion of a meal, unabsorbed nutrients may reach the distal intestine partly after the termination of the prandial period, i.e., in the presence of interdigestive motor and secretory patterns. To determine if interdigestive motility and pancreatic enzyme secretion are modulated by the delivery of nutrient into the ileal lumen, six fasting volunteers were intubated with an oroileal multilumen tube system that permitted multiple small intestinal manometry, gastric and duodenal aspiration, and perfus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 8 publications
1
10
0
2
Order By: Relevance
“…22 A function of the ileal brake in the physiological regulation of gastrointestinal motility and secretion has been proposed. 23 The effect of lipids administered into the small intestine on satiety and food intake in humans has been studied previously by Welch et al 8,12 These authors demonstrated that infusion of fat in the ileum caused a reduction in food intake in healthy volunteers.…”
Section: Discussionmentioning
confidence: 97%
“…22 A function of the ileal brake in the physiological regulation of gastrointestinal motility and secretion has been proposed. 23 The effect of lipids administered into the small intestine on satiety and food intake in humans has been studied previously by Welch et al 8,12 These authors demonstrated that infusion of fat in the ileum caused a reduction in food intake in healthy volunteers.…”
Section: Discussionmentioning
confidence: 97%
“…In this context, ileal lipid perfusion in 12 healthy volunteers resulted in dose-dependent inhibition of both pancreatic enzyme and bile secretion with unchanged intestinal motor activity [7,11,12].…”
Section: Physiology Of Pancreatic Enzyme Releasementioning
confidence: 99%
“…These peptides are released from the distal intestinal mucosa in response to a meal or intraileal nutrients (fig 4). 20 62-66 Ileal perfusion of lipids inhibits secretory and motor functions of upper gastrointestinal organs both in the interdigestive state 67 and during weak or moderate endogenous stimulation ( fig 5). 17 68-72 In addition, there are several studies suggesting comparable inhibitory effects of 12 60-100 26 42 51 -150 12 Data are derived from studies using test meals with 300-600 kcal and using no or only low marker perfusion rates ((3 ml/min).…”
Section: Initiation and Termination Of Digestive Enzyme Responsementioning
confidence: 99%